Analisa Kuat Tekan Bio Batu Bata Tanpa Bakar Dengan Memanfaatkan Lumpur Limbah IPA Km. 8 Kota Balikpapan - Az'Zahrah, Yuninda; Indriani, Andi Marini; Utomo, Gunaedy Utomo (Jurnal Teknologi Terpadu, 2024)
IPA waste sludge contains pollutants that can damage rivers. To reduce this, this research focuses on using mud to make bricks. This research also aims to make bricks without burning to minimize air pollution. Generally, bricks made without burning use cement to strengthen their strength. However, this research explores using biocemented Bacillus huizhouensis bacteria as a substitute for cement to strengthen bricks without burning. By adding a bacterial solution to the brick mixture, research found an increase in compressive strength of 59.78%, which was 1.47 MPa compared to normal bricks without bacterial reinforcement of 0.92 MPa. This study shows the potential for using the bacteria Bacillus huizhouensis to increase the strength of bricks while reducing pollution.